El teatre procedent del Principat representat a València (1833-1936) - Garcia Frasquet, Gabriel (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: Catalonian Theatre is translated into Spanish when performed in València. This is a clear cofirmation of the failure of the «Renaixença Valenciana».